2016
DOI: 10.1371/journal.pbio.2001015
|View full text |Cite
|
Sign up to set email alerts
|

Modifiers of the Genotype–Phenotype Map: Hsp90 and Beyond

Abstract: Disruption of certain genes alters the heritable phenotypic variation among individuals. Research on the chaperone Hsp90 has played a central role in determining the genetic basis of this phenomenon, which may be important to evolution and disease. Key studies have shown that Hsp90 perturbation modifies the effects of many genetic variants throughout the genome. These modifications collectively transform the genotype–phenotype map, often resulting in a net increase or decrease in heritable phenotypic variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…These metabolites, together with the parental prototypes, also served as a test set to assess the impact of Hsp90 inhibitors in vivo using an axolotl ETR assay. While developmental abnormalities have been observed in many organisms (including zebrafish administered Gdm [18] ) when Hsp90 activity is reduced below critical levels, [19] our results demonstrate that Gdm can be administered at a dose that blocks regeneration without overtly affecting development. This study implicates Gdm as a useful reagent to probe the role of Hsp90 in axolotl tail regeneration and suggests low dose Gdm could be used in a sensitized, ETR chemical genetic screen to identify new Hsp90 modulators.…”
mentioning
confidence: 61%
“…These metabolites, together with the parental prototypes, also served as a test set to assess the impact of Hsp90 inhibitors in vivo using an axolotl ETR assay. While developmental abnormalities have been observed in many organisms (including zebrafish administered Gdm [18] ) when Hsp90 activity is reduced below critical levels, [19] our results demonstrate that Gdm can be administered at a dose that blocks regeneration without overtly affecting development. This study implicates Gdm as a useful reagent to probe the role of Hsp90 in axolotl tail regeneration and suggests low dose Gdm could be used in a sensitized, ETR chemical genetic screen to identify new Hsp90 modulators.…”
mentioning
confidence: 61%
“…Such studies led to another hypothesis; that Hsp90 might not be a capacitor but a "genetic modifier" that has many interacting clients and can modify the genetic interaction network when the function is impaired (Geiler-Samerotte, Sartori, & Siegal, 2018). A recent study comparing effects of different genetic backgrounds has revealed that there are potentially numerous "genetic modifiers" in a genome (Paaby et al, 2015;Schell, Mullis, & Ehrenreich, 2016). Such a notion is consistent with Conrad Hal Waddington's original views on this, that it was not correct to assign a single functional role for each gene (Loison, 2018).…”
mentioning
confidence: 99%
“…An initial single dose screen revealed Gdm to completely inhibit tail regeneration with no Ratio [b] (23/24) Yield [c] of 23 effect observed for all of the other test agents.S ubsequent studies revealed ac lear dose-response for Gdm, with developmental abnormalities and toxicity observed at the highest dose (10 mm), inhibition of regeneration at intermediate doses,a nd no effect on regeneration at the lowest dose (0.1 mm ;F igure 2). In summary,m etabolic profiling led to the discovery of new Gdm analogues and as et of cyclopentenone macrolactams.T he development and implementation of ac obaltmediated benzilic acid rearrangement served as akey feature in mccrearamycin structure validation and highlights the potential synthetic utility in the context of 2-hydroxyquinonecontaining complex natural products.T hat cyclopentenone formation requires distinct conditions may also implicate au nique biosynthetic pathway.T hese metabolites,t ogether with the parental prototypes,also served as atest set to assess the impact of Hsp90 inhibitors in vivo using an axolotl ETR assay.W hile developmental abnormalities have been observed in many organisms (including zebrafish administered Gdm [18] )w hen Hsp90 activity is reduced below critical levels, [19] our results demonstrate that Gdm can be administered at ad ose that blocks regeneration without overtly affecting development. This study implicates Gdm as auseful reagent to probe the role of Hsp90 in axolotl tail regeneration and suggests low dose Gdm could be used in as ensitized, ETR chemical genetic screen to identify new Hsp90 modulators.…”
Section: Angewandte Chemiementioning
confidence: 51%